2020
DOI: 10.31004/jote.v1i2.514
|View full text |Cite
|
Sign up to set email alerts
|

DAMPAK EFIKASI DIRI TERHADAP PROSES & HASIL BELAJAR MATEMATIKA (The Impact Of Self-Efficacy On Mathematics Learning Processes and Outcomes)

Abstract: Kompetensi dalam pemecahan masalah matematika tentunya harus dimiliki oleh setiap siswa dalam menyelesaikan soal-soal matematika. Banyak persepsi di kalangan peserta didik yang menyatakan bahwa matematika adalah pelajaran yang sulit. Oleh karena itu dalam hal ini, efikasi diri sangat diperlukan untuk mengatasi masalah tersebut. Efikasi diri merupakan keyakinan yang dimiliki oleh seseorang tentang seberapa besar kemampuan yang dimilikinya untuk menyelesaikan suatu tugas pembelajaran. Siswa dengan efikasi diri y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
2
14
0
13
Order By: Relevance
“…(1) Students' self-efficacy will form students' mathematical skills in solving mathematical problems (Maulyda, 2020), (2) with high self-efficacy, the assumption that learning mathematics is difficult, stressful and stressful, and tedious, will be able to reduced or even eliminated by the students themselves. (3) the implementation of mathematics lessons in class is influenced by students' selfefficacy for learning mathematics itself (Ningsih & Hayati, 2020). Self-efficacy also has a decisive role in mediating student achievement (Pajares & Kranzler, 1995;Randhawa et al, 1993).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Students' self-efficacy will form students' mathematical skills in solving mathematical problems (Maulyda, 2020), (2) with high self-efficacy, the assumption that learning mathematics is difficult, stressful and stressful, and tedious, will be able to reduced or even eliminated by the students themselves. (3) the implementation of mathematics lessons in class is influenced by students' selfefficacy for learning mathematics itself (Ningsih & Hayati, 2020). Self-efficacy also has a decisive role in mediating student achievement (Pajares & Kranzler, 1995;Randhawa et al, 1993).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Such a situation can be related to Mathematics Self Efficacy, namely the ability to self-skill to manifest enthusiasm, self-confidence, confidence in oneself, and capable of introspection (Sari, 2020). Self-efficacy is a vital element in influencing students' mathematics learning outcomes (Ningsih & Hayati, 2020). Another study showed a significant impact of self-efficacy on mathematical problem solving (Somawati, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Self efficacy adalah kemampuan seseorang dalam meyakini kemampuan dirinya sendiri untuk memecahkan suatu permasalahan atau kondisi yang sedang dihadapinya. Hal ini sejalan dengan pendapat Wahyu F. Ningsih dan Isnaria R. Hayati [7] self efficacy merupakan keyakinan diri seseorang akan kemampuannya dalam menyelesaikan masalah, menyelesaikan tugas tanpa membandingkan dengan kemampuan orang lain sehingga dapat mencapai keberhasilan dalam prestasi belajar. Seseorang yang memiliki self efficacy baik akan lebih percaya diri dalam menyelesaikan tugas-tugas yang dihadapinya, sebab individu tersebut yakin akan kemampuan yang dimilikinya maka akan memungkinkan individu itu memiliki kemandirian belajar yang lebih baik [8].…”
Section: Tinjauan Pustakaunclassified
“…Salah satu referensi yang penting yaitu pendapat Ningsih & Hayati (2020) bahwa sebuah aspek afektif penting dari belajar adalah self efficacy. Menurut Oktariani (2019) self efficacy adalah keyakinan individu pada kemampuan mereka untuk melakukan sesuatu.…”
unclassified
“…Menurut Ningsih & Hayati (2020) self efficacy siswa terhadap tugas dalam pelajaran matematika cenderung rendah. Hal ini ditandai dengan munculnya citra matematika sebagai mata pelajaran yang sulit.…”
unclassified